Increased incidence of chronic lung disease and respiratory sequelae in growth restricted versus appropriately grown preterms - Sehgal, Kartik; Sehgal, Kunal; Tan, Kenneth (Indian Journal of Child Health, 2021)
Background: Fetal growth restriction (FGR) affects 5–10% term gestational age pregnancies. When accompanied by prematurity, FGR infants have significantly greater risk of perinatal morbidity and/or mortality compared to non-growth restricted preterm infants. Aim: Current study aimed to ascertain the incidence FGR among premature infants and its association with respiratory morbidity. Methods: Institution database for preterm infants of 23–31+6 weeks of gestation was accessed. FGR infants were compared with gestation/sex matched appropriately grown infants. Results: During the period 2016–2018, 973 infants between 23 and 31+6 weeks gestation were admitted amongst whom, 206 (27%) were FGR. Between 28 and 31+6 weeks gestation, approximately 1/3rd were FGR. Gestation and birth weight of the FGR and appropriately grown cohorts were 30.2±0.2 versus 30.1±0.2 weeks (p=0.8) and 1132±43 versus 1499±54 g (p